2019
DOI: 10.18805/ajdfr.dr-1407
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Evaluation and Determination of Physical and Functional Properties of Millets. (Ragi and Pearl Millet)

Abstract: The study determined the physical properties of finger millet (FM) (Eluesine coracana) grains and the functional properties of FM flour. Physical properties such as colour attributes, sample weight, bulk density, true density, porosity, surface area, sample volume, aspect ratio, sphericity, dimensional properties and moisture content of grain cultivars were determined. Water absorption capacity (WAC), bulk density (BD), dispersibility, viscosity and micro-structure of FM flours were also evaluated. Data collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Usman et al [ 55 ] stated that the low viscosity of fermented FM flours indicates that the flour is suitable for making weaning foods for new-borns. Both cold and cooked paste values obtained in native FM flour were similar to those obtained by Ramashia [ 56 ] and Pawase et al [ 57 ] for fortified and unfortified FM flours. These findings were also in consistent with Onweluzo and Nwabugwu [ 33 ], who studied how SF affects the viscosity of pearl millet flour.…”
Section: Resultssupporting
confidence: 87%
“…Usman et al [ 55 ] stated that the low viscosity of fermented FM flours indicates that the flour is suitable for making weaning foods for new-borns. Both cold and cooked paste values obtained in native FM flour were similar to those obtained by Ramashia [ 56 ] and Pawase et al [ 57 ] for fortified and unfortified FM flours. These findings were also in consistent with Onweluzo and Nwabugwu [ 33 ], who studied how SF affects the viscosity of pearl millet flour.…”
Section: Resultssupporting
confidence: 87%
“…Understanding the physicochemical characteristics of millet cultivars is crucial from a processing and nutritional security perspective. One of the key factors in food processing, packing, storage, and transportation operations, as well as in a number of post-harvest processes involving cereal grains, is physicochemical qualities 15 . The various physical properties is observed and shown in Tables 1, 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of fermentation and germination on the carbohydrates of pearl millet revealed that germination greatly increases the total soluble sugar concentration, as well as the reducing and non-reducing sugar concentration. When homogenized and autoclaved, the germinated slurry substantially increased the soluble sugars and decreased starch [ 49 , 59 ]. The main reason for reduced starch could be due to the starch hydrolysis during the germination and autoclaving process, resulting in a higher concentration of soluble sugars.…”
Section: Effect Of Processing On Nutritional Properties Of Milletsmentioning
confidence: 99%